Supported Gold Nanoparticles as Catalysts for the Oxidation of Alcohols and Alkanes - Carabineiro, Sónia A. C. (Frontiers in Chemistry, 2019)
Supporting gold nanoparticles have shown to be extremely active for many industrially important reactions, including oxidations. Two representative examples are the oxidation of alcohols and alkanes, that are substrates of industrial interest, but whose oxidation is still challenging. This review deals with these reactions, giving an insight of the first studies performed by gold based catalysts in these reactions and the most recent developments in the field.